On some new generalized difference sequence spaces on seminormed spaces defined by a sequence of Orlicz functions - Bektas, Cigdem A. (Versita, 2011)
In this paper we define the sequence space l(M) (Delta (upsilon) (m) , p, q, s) on a seminormed complex linear space, by using a sequence of Orlicz functions. We study some algebraic and topological properties. We prove some inclusion relations involving l(M) (Delta (upsilon) (m) , p, q, s).
Keywords: sequence of Orlicz functions; sequence spaces; difference sequence spaces